MODEL LAYANAN BIMBINGAN KELOMPOK BERBASIS KECAKAPAN HIDUP UTUK MENINGKATKAN ENTREPRENEURSHIP SISWA SMK MUHAMMADIYAH SOLO - Hera Heru S.S, Ulul Azam (UNIVERSITAS SLAMET RIYADI, 2015)
Entrepreneurship is an important element which is needed by everyone, includes Vocational HighSchool students’, especially when they run on the job trainning. The purpose of the research isthe product of group guidance service model that effectively enhances Vocational High Schoolstudents’ entrepreneurship. This is a kind of Research and Development (R & D) research. Theresult of preliminary study shows that the group guidance service which is held in SMKMuhammadiyah Solo is not ideal yet and doesn’t integrate the life skills values in the process.This condition is becoming one of the factors so the students reach minimum level ofentrepreneurship. Based on that preliminary study, the group guidance service based on life skillsto enhance students’ entrepreneurship is being developed. The trial result in the field shows thatthe students’ entrepreneurship is getting higher. The average score of the first evaluation is 149,2and the average score of the final evaluation is 193,7 or it can be said it raised up to 44,5 points.It means that the service model which is developed is effective to enhance Vocational HighSchool students’ entrepreneurship.Key words : group guidance service model, life skills, and entrepreneurship